Penerapan Evidence Base Nursing Practice Skrining Diabetic Sensorimotori Polineuropathy (DSPN) di UPT RSUD Labuang Baji Makassar - Sri Sakinah; Yani Sofiani; Ninik Yunitri (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Diabetes Mellitus is a degenerative disease, if not treated properly it can have a negative impact on complications in various organ systems in the body (Syahid, 2021). One of the complications of diabetes that often occurs is neuropathy (nerve damage) in the feet which increases the incidence of foot ulcers, infections and even the need for foot amputation (Sianipar, 2023). The aim of this research is to prepare Standard Operating Procedures (SPO) for the implementation of EBNP regarding Diabetic Sensorimotor Polyneuropathy (DSPN) Screening in Type 2 Diabetes Mellitus patients. The number of respondents involved in implementing this EBNP was 14 people. In the implementation of EBNP, Diabetic Sensorimotor Polyneuropathy (DSPN) screening was carried out using the mTSN (Modified Toronto Clinic Score Neuropathy) instrument which aims to assess whether there are symptoms of neuropathy and no symptoms of neuropathy. DSPN screening is carried out based on Standard Operating Procedures (SOP). Based on the results of the two instrument tests between mTCSN and mNSI-E using the undercurve test, it can be concluded that the mTCSN instrument has a higher sensitivity value with a value of 0.909, while the sensitivity value for the mNSI-E instrument is smaller than the mTCSN instrument with a value of 0.571. So, to screen for neuropathy it is more effective to use the mTCSN instrument because the sensitivity score is higher. Keywords: Diabetes Mellitus, Screening, Polyneuropathy, DSPN  ABSTRAK Diabetes Melitus merupakan penyakit degeneratif bila tidak ditangani dengan baik dapat berdampak buruk menjadi komplikasi pada berbagai sistem organ dalam tubuh (Syahid, 2021). Salah satu komlikasi dari diabetes yang sering terjadi adalah Neuropati (kerusakan saraf) dikaki yang meningkatkan kejadian ulkus kaki, infeksi dan bahkan keharusan untuk amputasi kaki (Sianipar, 2023). Tujuan penelitian ini adalah tersusunnya Standar Prosedur Operasional (SPO) pelaksanaan EBNP tentang Skrining Diabetic Sensorimotori Polyneurophaty (DSPN) pada pasien Diabetes Melitus Tipe 2. Jumlah responden yang terlibat pada pelaksanaan EBNP ini adalah 14 orang. Pada pelaksanaan EBNP ini telah dilakukan skirining Diabetic Sensorimotori Polineuropathy (DSPN) dengan menggunakan instrumen mTSN (Modified Toronto Clinic Score Neuropathy) yang bertujuan untuk menilai ada gejala neuropati dan tidak ada gejala neuropati. Skrining DSPN dilakukan berdasarkan Standar Operasional Prosedur (SOP). Berdasarkan hasil kedua uji intrumen antara mTCSN dengan mNSI-E menggunakan uji undercurve, maka dapat disimpulkan, instrumen mTCSN memiliki nilai sensitivitas yang lebih tinggi dengan nilai 0.909, sedangkan nilai sensitivitas pada instrumen mNSI-E lebih kecil dari instrumen mTCSN dengan nilai 0.571. Maka, untuk melakukan skrining neuropathylebih efektif digunakan instrumen mTCSN karena skor sensitivitasnya lebih tinggi. Kata Kunci: Diabetes Mellitus, Skrining, Polyneurophaty, DSPN